Converting an Established Sida hermaphrodita Field into Arable Farming - Nicolai David Jablonowski; Benedict Ohrem; Michael Gitzen; Tobias Kollmann (Agronomy, 2024)
The long-term performance of perennial energy crops and their elimination is important for long-term planning and use of agricultural land. In this study, the elimination of a six-year-old Sida hermaphrodita (hereafter referred to as Sida) stock for agricultural reclamation was investigated over three years. Crop rotation using maize, winter wheat, and sugar beet, a catch crop, as well as mechanical–chemical treatments were employed according to agricultural practices. After soil grubbing at the beginning of the experiment and prior to further treatments, on half of the former Sida planting area, visible Sida roots were manually removed in addition to determining their potential effect on total resprouting. Prior to each crop harvest, resprouted Sida plants were counted. At harvest, by the end of the first year, 476 versus 390 resprouted Sida plants were found in the investigated areas of 315 m2 each, where preceding manual root removal either took place or not, respectively. This accounted for 76% and 62% of the initial Sida planted. In the second year, the overall number of resprouted Sida declined significantly, accounting for 15 and 11 plants (i.e., 2.4% and 1.8% of initially planted), and in the third year, only two and four residual plants (i.e., 0.3% and 0.6%) were found, representing an almost 100% Sida elimination rate. We conclude that additional root removal did not result in a significant difference in Sida regrowth compared to the mechanical–chemical treatments only. No impediments to harvesting and no loss of yield in any crops were observed due to resprouted Sida in the existing field crops. No Sida plants were found outside the initial field, indicating a low dispersion potential and invasiveness. The results show that successful recultivation of an established Sida stock is possible through common agricultural practices and that resprouting Sida plants did not negatively affect the subsequent crops.